Sports Versatility of Polish Footballers, Participants of League Games in 1927–1939 - Owsiański, Jarosław (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The players who played in the Polish football league in the interwar period were very versatile and talented, therefore they were also successful in other sports. The aim of the study was to assess the scale of this phenomenon. The mass development of football in Poland meant that there was a shortage of talented players in the struggle involving sports games, athletics or winter sports. The high level of physical fitness of the players predisposed them to participate in the competitions in sections of sports clubs other than football. The author presents detailed lists of footballers, participants in league competitions in the years 1927–1939, who became medallists of Polish championships in ice hockey, athletics, basketball, volleyball and handball. In addition, the biographies and achievements of the most versatile athletes are included.